2005
DOI: 10.1007/s11068-006-8730-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of calcium-independent phospholipase A2 (iPLA2) in monkey brain

Abstract: The present study was carried out to elucidate the distribution of calcium-independent phospholipase A(2) (iPLA(2)) in the normal monkey brain. iPLA(2) immunoreactivity was observed in structures derived from the telencephalon, including the cerebral neocortex, amygdala, hippocampus, caudate nucleus, putamen, and nucleus accumbens, whereas structures derived from the diencephalon, including the thalamus, hypothalamus and globus pallidus were lightly labeled. The midbrain, vestibular, trigeminal and inferior ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 32 publications
1
57
0
Order By: Relevance
“…Ultrastructurally, the mitochondrial and presynaptic membranes, both of which contain PC with DHA (Omoi et al, 2006;Mitchell et al, 2007), were affected, and tubulovesicular structures were formed in the middle and ends of axons. The vulnerability of mitochondrial and presynaptic membranes might be explained by the selective localization of iPLA 2 ␤ in mitochondria (Seleznev et al, 2006) and synapses (Ong et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructurally, the mitochondrial and presynaptic membranes, both of which contain PC with DHA (Omoi et al, 2006;Mitchell et al, 2007), were affected, and tubulovesicular structures were formed in the middle and ends of axons. The vulnerability of mitochondrial and presynaptic membranes might be explained by the selective localization of iPLA 2 ␤ in mitochondria (Seleznev et al, 2006) and synapses (Ong et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…In the brain of iPLA 2 ␤-deficient mice, DHA metabolism is reduced at 4 months without overt neuropathology (Basselin et al, 2010), and an iPLA 2 ␤ inhibitor has been reported to attenuate linoleic acid (LA) incorporation of cardiolipin (CL) in rat heart (Zachman et al, 2010). In monkey brain, iPLA 2 ␤ is localized in axon terminals and dendritic spines of neurons (Ong et al, 2005). Although iPLA 2 ␤ also exists in various organs , no known non-neurological dysfunction has been reported in INAD (Gregory and Hayflick, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Principally, different pathways can generate PA: (1) hydrolysis of phospholipids via PLD (Bader and Vitale, 2009), (2) phosphorylation of diacylglycerol (DAG) by DAG kinase (Yang et al, 2011), and (3) acylation of lysophospholipids by lysophospholipid acyltransferases ). Lysophospholipids, substrates of the latter reaction, are generated under various physiological and pathophysiological situations at various cell organelles, e.g., the endoplasmic reticulum, Golgi apparatus, endosomes, and presynaptic terminals (de Figueiredo et al, 2001;Chambers et al, 2003;Ong et al, 2005;Rigoni et al, 2005;Rossetto and Montecucco, 2008;Schmidt and Brown, 2009;Oliveira et al, 2010;Vitale et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…8) are believed to result from degenerated ER or mitochondria. iPLA 2 ␤ has been reported to exist in and protect mitochondria (Seleznev et al, 2006), as well as being abundant in neurites and axon terminals (Ong et al, 2005), so its absence would contribute to damage targeting mitochondria in axons and synaptic terminals, leading to degeneration of the axons and synaptic terminals. Some individuals with NBIA, formerly known as HallervordenSpatz syndrome, have a mutation of the pantothenate kinase 2 (PANK2) gene (Zhou et al, 2001).…”
Section: Discussionmentioning
confidence: 99%